Teachers as Agents of Religious Moderation: A Study on the Use of Islamic Education Textbooks in Madrasah Aliyah - Khoirudin, Azaki; Sandiah, Fauzan Anwar (Studi Multidisipliner: Jurnal Kajian Keislaman, 2025)
This study examines the textbooks and teachers of PAI (Islamic Religious Education) in the process of transmitting Islamic religious knowledge at Madrasah Aliyah, Manado City. Manado City was chosen as one of the tolerant cities in Indonesia where the majority of the population embraces Christianity, while Muslims are a minority. The focus of this research is teachers' perception of textbooks, religious patterns, and teachers' agency in learning Islamic religious subjects. Qualitative methods through in-depth interviews are used as instruments to csollect and analyze research data. The results of this study show that the 2013 PAI Curriculum textbook published by the Ministry of Religion of the Republic of Indonesia is too complex, but not in-depth, so that teachers need to innovate to find teaching resources from the internet. PAI teachers in the city of Manado reject the perception of Madrasah which has been considered as an institution that produces extreme ideas in religion. On the contrary, this study shows religious teachers as agents of religious moderation. Classrooms and teachers become mediators and facilitators for students who gain intolerant-exclusive religious understanding from offline and online recitations. Islamic religious learning in madrassas in the city of Manado is a mechanism to reduce radicalism by making the classroom an arena for discourse to develop religious moderation in the city of Manado.